Autophagy in Current Trends in Cellular Physiology and Pathology - Gorbunov, Nikolai V.; Schneider, Marion (IntechOpen, 2016)
Autophagy in Current Trends in Cellular Physiology and Pathology is addressed to one of the fundamental molecular mechanisms - autophagy- evolutionarily adopted by cells for processing of unnecessary or malfunctioned constituents and shaping intracellular structures, adjusting them to environmental conditions, aging, disease, neoplasia, and damages over their life period. Particular attention is paid to autophagy-mediated barrier processes of selective sequestration and recycling of impaired organelles and degradation of invading microorganisms, that is, the processes sustaining intrinsic resistance to stress, tissue degeneration, toxic exposures, and infections. The presented topics encompass personal experience and visions of the chapter contributors and the editors; the book chapters include a broad analysis of literature on biology of autophagy.